Genotypic evaluation of dent composite (Zea mays L.) half-sib progenies in late harvest crop conditions - Tozetti, André Dall' Oca; Osuna, Juan Ayala; Banzatto, David Ariovaldo (Pesquisa Agropecuaria Brasileira, 1995)
The present work was conducted at FCAV-UNESP, Câmpus de Jaboticabal, in late harvest crop time of 1991. One hundred interpopulational hybrids obtained from a top-cross between Dent Composite and Flint Composite populations were evaluated. The analyzed characteristics were: Spodoptera frugiperda damages, lodging, damaged ears percentage, and productivity. Estimates of heritability, variance between progenies and genetical gain for each character of available population were determined. Estimates of the progenies variance, like those from heritability for the different analysed characters, indicate that there is an adequate genetical variance for the utilization of that material on subsequent genetic breeding programs, though allowing genetical gains, on the following selection cycles for the characteristics: grain weight, lodging and damages caused by armyworm larvae, whereas for the other characteristics the obtained results were not satisfactory.